A single nucleotide polymorphism in the gene for GPR183 increases its surface expression on blood lymphocytes of patients with inflammatory bowel disease. (10th March 2021) - Ruiz, Florian; Wyss, Annika; Rossel, Jean‐Benoît; Sulz, Michael Christian; Brand, Stephan; Moncsek, Anja; Mertens, Joachim C.; Roth, René; Clottu, Aurélie S.; Burri, Emanuel; Juillerat, Pascal; Biedermann, Luc; et al.
Abstract : Background and Purpose: Single nucleotide polymorphism rs9557195 within the gene of the G protein‐coupled receptor Epstein‐Barr virus‐induced gene 2 ( EBI2/GPR183 ) has been associated with increased risk for inflammatory bowel diseases (IBD). GPR183 mediates the migration of intestinal immune cells and promotes colitis in animal models. Here, we study GPR183 surface expression of immune cells and associations of rs9557195 with GPR183 expression and IBD disease course. Experimental Approach: We recruited 27 IBD patients (15 with ulcerative colitis [UC] and 12 with Crohn's disease [CD]) and eight healthy volunteers (HV). GPR183 expression was measured by FACS in subtypes of peripheral blood mononuclear cells. We analysed IBD disease course in 2301 patients (1335 with CD and 966 with UC) of the Swiss IBD cohort study. Key Results: We found increased GPR183 expression in lymphocytes expressing chemokine receptors CCR6 or CCR9, implicated in IBD and on Th17 memory T cells. The GPR183 ligand 7α, 25‐dihydroxycholesterol and the CCR6 ligand CCL20 stimulated migration of memory T cells in an additive manner. Further, IBD patients with the CC allele of rs9557195 had higher GPR183 surface expression compared to individuals with the TT allele. Swiss IBD cohort study patients carrying the rs9557195‐CC allele had higher psoriasis rates compared to individuals with the TT allele. Conclusion and Implications: We demonstrate increased GPR183 surface expression on T cells with a potential role in gut inflammation. An SNP of the GPR183 locus was associated with GPR183 surface expression and psoriasis rates in IBD patients. Our data suggest a pro‐inflammatory role of GPR183 in IBD. LINKED ARTICLES: This article is part of a themed issue on Oxysterols, Lifelong Health and Therapeutics. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.16/issuetoc